Фінансовий ринок як рушій глобалізаційних змін та його зв'язок із рівнем фінансової безпеки - Онишко, Світлана Василівна; Богріновцева, Людмила Миколаївна (Національний університет «Острозька академія», 2023)
В статті обґрунтовано важливість реалізації діалектичного зв’язку фінансової безпеки і фінансового ринку, в основу якого покладено керовану інтегрованість їх стратегічних цілей та потенціалу. Наголошено на можливостях додаткового доступу як до механічних, характерних перебуванню фінансової безпеки і фінансового ринку у площині порівняно ізольованих систем, так і до органічних джерел, генерованих горизонтальними зв’язками у межах альтернативних шляхів розвитку фінансового ринку і фінансової безпеки які найповніше відповідаючи їх специфіці, одночасно органічно вплітаються в стратегію досягнення суспільних цілей. Це сприятиме зміцненню фінансової безпеки як основи відновлювального та подальшого поступального розвитку шляхом трансформації механізму розвитку із переважаючого нині мобілізаційного в інноваційний, який утверджує випереджаючі характеристики розвитку та активізує його інтенсивні джерела.

The study focuses its attention on the lack of effective implementation of the connection between ensuring financial security and the functioning of the financial market, which leads to the potential losses in solving the problems of socio-economic progress. For the most comprehensive consideration of the set of determinants that form the general course of development of the processes of ensuring financial security and the financial market, the special role of globalization is indicated. Having a deep impact on world social relations, their content, dynamics and various cause-and-effect relationships, globalization occupies an important decisive place in solving major problems of ensuring national security. At the same time, the role of the financial market as a driver of globalization processes dictates the need for practical implementation of the fundamental foundations and changes in the organization of the financial market related to globalization. The inherent system-forming function of the financial market regarding the financial system and the density of its integration into the financial space indicate its ability to contribute to or pose a threat to the stability of the financial system and the strengthening of financial security. It is substantiated that discovering the ways of accumulating the potential of both spheres is associated with the opening of additional access within the financial market not only to mechanical but to organic sources of strengthening financial security as well. It is noted that mechanical sources are characteristic of financial security and the financial market in the plane of relatively isolated systems, and organic sources are actively generated by horizontal links within the bounds of alternative ways of development of the financial market and financial security, most fully complying with their specifics and organically intertwining into the strategy of achieving social goals. It is emphasized that the conceptual transformation of relations in the "financial security - financial market" chain lies in the plane of dialectical interaction between them, based on the controlled integration of their strategic goals and potential. This transformation actively affects the functional and organizational models of financial security and financial market functioning, contributing to the overall transformation of their development mechanism from the currently prevailing mobilization one into an innovative one that asserts the advanced characteristics of development by activating intensive sources.
Keywords: глобалізація; фінансова безпека; фінансовий ринок; взаємозв’язок; стратегічні цілі; потенціал; трансформація; механізм; globalization; financial security; financial market; correlation; strategic objectives; potential; transformation; mechanism